ANALISIS HUBUNGAN PENYAKIT DEGENERATIF TERHADAP KEJADIAN STROKE - Rondonuwu, Rolly; Yoyoh, Imas; Nuraeni, Eni; Setiyawati, Yuyun (Ensiklopedia of Journal, 2025)
Abstract: Stroke is one of the leading causes of long-term disability and the second leading cause of death worldwide. The high incidence of stroke is influenced by various factors, one of which is the presence of degenerative diseases. The aim of this study was to analyze the relationship between degenerative diseases and stroke incidence. The study design used in this research was a case-control study. The study was conducted at Haji Medan General Hospital in September 2024. The case population consisted of all patients diagnosed with stroke, and the control population consisted of all patients admitted to the priority disease ward at Haji Medan General Hospital. The sample size was 112 respondents, comprising 56 cases and 56 controls. The sampling technique used in this study was Simple Random Sampling. Data analysis was performed using univariate and bivariate methods. The results of the study showed a significant association between a history of hypertension (p-value: 0.002) and a history of diabetes mellitus (p-value: 0.026) with the occurrence of stroke. It is recommended that healthcare workers actively engage with patients and the community to encourage them to regularly undergo health check-ups at health centers, clinics, or hospitals to monitor their blood pressure and blood sugar levels.Keywords: Diabetes mellitus, hypertension, stroke.